Perancangan Aplikasi E-Commerce pada Toko I’M Collection WTC Jambi - Nur Azmi Yati; Abdul Rahim (Jurnal Processor, 2017)
I'm Collection is one of the stores that sell women's clothing that is in Wiltop Trade Centre (WTC) Jambi BatangHari Block C No. 8-9. Marketing and sales system used by the store I'm Collection now the buyer must come directly to the store to see and buy goods. Based on interviews, the authors conclude that the sales process at this time creates difficulties for customers, which are located far apart the store I'm Collection. Customers would always want the ease or speed of the relevant information to facilitate their activities, one of them ordering or purchasing clothes on I'm Collection. The method used is the method of field research and interviews. This study produced a computerized application by using the main programming language PHP and My SQL Database. It is expected that these applications can help data processing system Sales and Sales Transactions that exist in the store I'm Collection WTC Jambi.